A De Novo Transcriptome Assembly of Ceratopteris richardii Provides Insights into the Evolutionary Dynamics of Complex Gene Families in Land Plants. (3rd March 2021) - Geng, Yuan; Cai, Chao; McAdam, Scott A.M; Banks, Jo Ann; Wisecaver, Jennifer H; Zhou, Yun
Abstract: As the closest extant sister group to seed plants, ferns are an important reference point to study the origin and evolution of plant genes and traits. One bottleneck to the use of ferns in phylogenetic and genetic studies is the fact that genome-level sequence information of this group is limited, due to the extreme genome sizes of most ferns. Ceratopteris richardii (hereafter Ceratopteris) has been widely used as a model system for ferns. In this study, we generated a transcriptome of Ceratopteris, through the de novo assembly of the RNA-seq data from 17 sequencing libraries that are derived from two sexual types of gametophytes and five different sporophyte tissues. The Ceratopteris transcriptome, together with 38 genomes and transcriptomes from other species across the Viridiplantae, were used to uncover the evolutionary dynamics of orthogroups (predicted gene families using OrthoFinder) within the euphyllophytes and identify proteins associated with the major shifts in plant morphology and physiology that occurred in the last common ancestors of euphyllophytes, ferns, and seed plants. Furthermore, this resource was used to identify and classify the GRAS domain transcriptional regulators of many developmental processes in plants. Through the phylogenetic analysis within each of the 15 GRAS orthogroups, we uncovered which GRAS family members are conserved or have diversified in ferns and seed plants. Taken together, the transcriptome database and analyses reported here provide an important platform for exploring the evolution of gene families in land plants and for studying gene function in seed-free vascular plants.